Reliability of a reactive agility test for youth volleyball players - Lima, R.; Rico-González, M.; Pereira, J.; Caleiro, F.; Clemente, F. (Polish Journal of Sport and Tourism, 2021)
Introduction. This was a cross-sectional study aiming to test the reliability of a new reactive agility test designed for youth volleyball players to improve both reaction time and hand-eye coordination.